Pemberdayaan Masyarakat dalam Identifikasi dan Pencegahan Diabetes Melitus - Dian Isti Angraini; Novita Carolia; Intanri Kurniati; Agustyas Tjiptaningrum; Sri Hasnawati (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2023)
Diabetes Mellitus (DM) is one of the chronic diseases which is the highest cause of death in Indonesia and the number of morbidities continues to increase so that the health costs of DM disease are also higher. Diabetes is a disease that can be controlled or prevented if it can be detected as early as possible, because diabetes is often associated with a person's lifestyle and diet which results in increased blood sugar levels in the body. The purpose of this activity is to empower the community, such as health cadres and community members in identifying and preventing diabetes mellitus. The method that will be carried out is health education through lectures and interactive discussions, and videos. This activity was carried out for 1 day and took place in Sumberrejo Village, Kemiling sub-district, Bandar Lampung City. Participants totaled 30 people who were village officials, health cadres and community members. The results of the evaluation of the service implementation found that there was an increase in the participants' understanding of 93.33% to a good understanding, 6.67% of the participants had a fairly good understanding, and no participants had a poor understanding of the signs and symptoms, risk factors, and prevention of DM. The average pretest result was 58.2 and there was an increase in the posttest result which was 84.5. Based on the analysis using the Wilcoxon test, it was found that there was a statistically significant mean difference in the participants' pretest and posttest scores (p=0.001). Community empowerment activities in identifying and preventing DM have proven effective.